The role of customary law in Environmental Conservation: A Case Study in Dayak Indigenous communities - Hendri Khuan; Revi Sesario; Andi Kurniawan (Journal of Adat Recht, 2025)
This research examines the role of Dayak customary law in environmental conservation, focusing on sustainable natural resource management. It explores how practices such as land-use restrictions, sacred forest protection, and conservation rituals contribute to ecosystem preservation. The study also identifies conflicts between customary law and national policies, particularly regarding land tenure and resource exploitation by industries. Using a normative legal approach, the research analyzes Indonesia’s legal framework, including the 1945 Constitution, the Forestry Law, and the Environmental Protection Law. Through case studies in Kalimantan, the study highlights the effectiveness of these practices in conserving the environment. The findings indicate that while customary law plays a crucial role in conservation, its potential is hindered by insufficient recognition and alignment with national laws. The study recommends enhancing the formal recognition of customary law through clearer legal frameworks, improving collaboration with local governments, and providing capacity-building programs for indigenous communities to ensure sustainable resource management.